OPTIMALISASI FUNGSI KELUARGA DALAM PENCEGAHAN FENOMENA KEHAMILAN YANG TIDAK DIINGINKAN PADA REMAJA - Nurhandayani, Fitri (IKIP Siliwangi, 2022)
AbstractÂ Adolescence is a transition from childhood to adulthood. The role and function of the family is very important for adolescence. Lack of attention and supervision from parents during adolescence will cause problems, such as the occurrence of unwanted pregnancies. In Indonesia, this phenomenon is often referred to as Married By Accident (MBA) or a marriage that occurs due to an unwanted pregnancy. The purpose of this study was to describe the optimization of family functions in preventing the phenomenon of unwanted pregnancy in adolescents. The research theories used are structural functional theory, ecological theory and community education theory. The research method used is a qualitative approach with a descriptive method. Data collection techniques through observation, interviews and documentation. The main reason for using this instrument is to observe the phenomenon of problems faced by families related to optimizing family functions in preventing unwanted pregnancies in adolescents and to obtain research data as material for analysis. The results of this study describe the optimization of family functions on adolescent growth and development and psychological maturity so as to avoid the impact of unwanted pregnancy cases. The conclusion of this study is that the role of the family greatly affects the maturity of adolescents, both young women and young men.